A numerical and experimental investigation on the evolution of three-dimensional surface topography of 12Cr2Ni4A steel in shot peening. (October 2021) - Zhao, Jiuyue; Tang, Jinyuan; Ding, Han; Shao, Wen; Zhao, Xing; Liu, Huaming; Jiang, Tingting
Abstract: Shot peening is widely used as a surface strengthening technology as it can enhance fatigue life of mechanical components by introducing reasonably distributed compressive residual stress. However, improper selection of processing parameters would inevitably lead to deterioration of the surface quality, and negatively affect on the fatigue performance. In this paper, a random multiple-shot model was proposed to accurately calculate the evolution of 3D surface topography 12Cr2Ni4A steels during shot peening. The simulated results are in good agreement with the experimental results, with an error of less than 10%. It is found that surface roughness parameter Sa first increases significantly and then decreases slowly with the increase of peening time. Moreover, the surface height after shot peening obeys a normal distribution and the 3D surface roughness is positively correlated with the initial roughness.